The Influence Of The Teacher's Ability To Use Computer-Based Media On Student Attention In Islamic Religious Education Learning At Public Junior High School (SMPN) 2 Sidrap - Muhammad Hijaz Tahir; Muhammad Arsal Hijaz; Sam Hermansyah (Yayasan Adra Karima Hubbi, 2023)
Background. Computer-based media enhances material acceptance and retention, facilitating teachers in efficient material storage and direct student engagement. Utilizing visuals and audio, it directly appeals to sight and hearing senses. Hence, the research titled